PEMETAAN DAN ANALISIS KOMPETENSI INTI UKM BATIK DI KABUPATEN PURBALINGGA DENGAN PENDEKATAN VALUE CHAIN - Weni Novandari (Jurnal Ekonomi Dan Bisnis, 2015)
The aimed of this study are 1) To identify the profile ofSMEsin Purbalingga batik which includes the amount, location, production capacity, product type, amount of labor, raw materials and production facilities.2) To identify the core competencies of SMEsin Pubalingga batik by Value Chain approach. Data collection method susedin this study is the triangulation method, consist of : observation,documentationandinterview. Qualitativedescriptiveanalysis used to analyzethe elements inthe frameworkofValueChain Management thatcan bedefinedas a core competencyof SMEsbatikin Purbalingga.The resultsshown 1) Profilesobtainedin Purbalingga’s small enterprises batikwhich has anumberofmore or lessas many as 400people spreadacross multiplecenters ofbatik, which isin Bobotsari, Bojongsari, Kalimanah, Karangmoncol and Kemangkon District. Turn over estimated peryear batiki saround Rp 4,595,200,000 to Rp 9.28 billion. Products resulted includebatikcloth, sinjang, and tablecloths. The majority of batik craftsmen still run the business in atraditional way. 2) Basedon the value chain analysis, core competencies that can be the basis for competitive advantagein purbalingga batik SMEs are The Speed and the craftsmen's apilityin theprocess of ofmaking batike specially on stage nyanting skills that is noteasyto be imitated byother batik craftsmen.Keywords : SMEsbatik, Core Competence, Value Chain